Engineering Properties of Undisturbed Gypseous Soil Percolated by Olive Oil (Eurasian Journal of Engineering and Technology, 2022)
This study investigates the effect of olive oil percolation on the shear strength of undisturbed gypseous soil upon wetting. Three samples of soil were taken at depth 1.5m from different locations at Saladin province in Iraq: Tikrit city sample (S1) with gypsum content 26.6%, Al Alam area sample (S2) with 42.2% gypsum and Al Door area sample (S3) with 61.7% Gypseous content. The main aim is to explore the effect a non-destructive additive that maintains the structure of gypsum soil and to check the possibility of forming water-resistant gypsum soil. Direct shear tests were conducted for four cases: semi dry soil in its natural water content (untreated), soil soaked in water, soil soaked in olive oil (treated), and finally the treated soil soaked in water after left in ambient temperature for 10 days (soaked in water after treated). One sample is left for 8 months to examine the long-term effect of oil. Results show that on average the soil cohesion is reduced by 70% when soaked in water, 20% when soaked in olive oil, and 35% when treated soil soaked in water. However, the angle of internal friction exhibits differently with less reduction of 4%, 6% and 15% respectively. For the samples that were treated and left for 8 months, soil cohesion and angle of internal friction were reduced by 24%, and 27% respectively